Dissemination of fermented technology and diet formulation to provide economical feed in Sikka District - I Kadek Yoga Kertiyasa; Dewi Elfrida Sihombing; Ni Nengah Suryani (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2026)
The initiation of this community service was driven by the challenges faced by livestock farmers in Sikka Regency, East Nusa Tenggara (NTT). One of the main issues in small-scale livestock farming is the availability of feed, both in terms of quality and quantity. Although Sikka Regency has abundant agricultural byproducts, such as banana stems, cassava leaves and stems, and papaya leaves, these resources remain underutilized due to farmers’ limited knowledge and technical skills in processing them into livestock feed. The target group for this program are pig farmers. This community service program aims to support the production of livestock feed by maximizing the use of agricultural byproducts to ensure year-round availability. The implementation methods included extension activities, dissemination of fermentation technology, ration formulation, and guidance on feed production. The results demonstrate that farmers were able to produce livestock feed from banana stems using fermentation technology. The program enabled farmers to access a lower-cost alternative compared to commercial feed, priced at Rp 7,230 per kilogram based on the proposed ration formulation. This community service activity is expected to encourage farmers to further utilize locally available agricultural byproducts as feed resources.